2021
DOI: 10.1109/access.2020.3047851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Greenhouse Design Parameters on the Heating and Cooling Requirement of Greenhouses in Moroccan Climatic Conditions

Abstract: Protected crop production is rapidly expanding in the Mediterranean Basin, and particularly in Morocco. Increased local and overseas demand for these products led to a rapid development in greenhouse usage encouraged by government policies. The aim of this study is to investigate key design parameters that affect the thermal behavior and the heating/cooling energy need of a greenhouse situated in Agadir (Morocco). The parameters include the cladding material characteristics, shape, orientation, and air change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…BES tools are used to investigate the effect of the different parameters on greenhouse microclimate and predict the most favourable operating conditions that minimise the energy consumption. With TRNSYS, several studies have reported the effect of the regime type, environmental control systems, covering materials, greenhouse shape, and orientation on the thermal performance of the greenhouse, with no consideration to the radiation modes [27][28][29]. The accurate modelling of the solar heat gains in the greenhouse with the different radiation modes in TRNSYS is also an important aspect that should be considered.…”
Section: Scope Of the Studymentioning
confidence: 99%
“…BES tools are used to investigate the effect of the different parameters on greenhouse microclimate and predict the most favourable operating conditions that minimise the energy consumption. With TRNSYS, several studies have reported the effect of the regime type, environmental control systems, covering materials, greenhouse shape, and orientation on the thermal performance of the greenhouse, with no consideration to the radiation modes [27][28][29]. The accurate modelling of the solar heat gains in the greenhouse with the different radiation modes in TRNSYS is also an important aspect that should be considered.…”
Section: Scope Of the Studymentioning
confidence: 99%
“…have been used [1]- [3]. Although the cost of power generation through these processes is low, the carbon dioxide and dioxide flow generated in the process of power generation have caused environmental pollution, and the greenhouse effect [4], [5]. While the cost of nuclear power generation is cheaper, it also generates radioactive waste during the power The associate editor coordinating the review of this manuscript and approving it for publication was Zhilei Yao .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Çakir et al [18] studied the magnitude of solar radiation intercepted by the greenhouse cover for five greenhouses shapes, different dimensions and orientation are investigated for each shape and the greenhouse with the highest solar radiation gaining rate is introduced. Choab et al [19] performed a study to examine the effect of greenhouse design parameters including the specification of cover material, shape and orientation of the greenhouse on the thermal performance and required energy for heating and cooling the greenhouse in Agadir Morocco. TRANSYS software was used for greenhouse modeling.…”
Section: Introductionmentioning
confidence: 99%